(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aims to determine the view of the medical ethics code regarding the doctor’s profession as the chemical castor of child sexual offenders who has been decided by the court as mandated by Article 82 A paragraph (2) of Law Number 17 of 2016 concerning Child Protection in conjunction with Article 9 of Government Regulation Number 70 of 2020 concerning Procedures for Implementing Chemical Castration, Installing Electronic Detection Devices, Rehabilitation and Announcement of the Identity of Perpetrators of Sexual Violence Against Children. This research is a normative legal research. Based on the results, it is known that theoretically related to the authority of the medical profession as a party ordered by law to carry out the castration process for perpetrators of sexual abuse against children who have been decided by the court is contrary to the principles contained in the medical code of ethics and oaths. doctor, in this case the presence of such a thing makes the doctor feel that he is not doing his profession in accordance with the Code of Medical Ethics which has been agreed upon and highly upholds moral values, one of which is “informed consent” or consent from family or patient. all actions that result in a decrease in the patient’s physical endurance, although not necessarily reduce his psychological endurance. Second, that chemical castration is not a type of medical service but a punishment, so it is not the domain of medical or health personnel to do it.